Analysis of the genotoxic effect of alcohol consumption, using the micronucleus test in students at Cesumar University, Ponta Grossa (Research, Society and Development, 2025)
The exposure to genotoxic substances, such as alcohol, can cause damage to genomic DNA, leading to various types of cellular alterations. The Micronucleis are DNA fragments that are separated of the nucleus resulting in cellular instability. Their presence may be associated with several diseases, such as various types of cancer, Alzheimer's and AIDS. For this reason, and considering the high consumption of alcohol by university students, the objective of this project is to study quantitatively and qualitatively the presence of micronuclei in cells and their relationship with alcohol, through the micronucleus test in students of Unicesumar. A questionnaire was elaborated based on the AUDIT test to select through life habits the appropriate candidates for this study and divided in two groups, 15 people in the exposed group and 15 in the control group. After the collection of biological material, oral mucosa, microscopic and statistical analysis of this anomaly was performed, through the Tukey test. After analysis, it was possible to observe the direct relationship that alcohol, as well as other genotoxic agents have with the mutations that occurred in the nuclei of the cells of the oral mucosa. This project involves research with human beings and, therefore, was approved by the ethics committee according to the Certificate of Presentation and Ethical Appreciation (CAAE): 59946422.1.0000.5539.